Enterprise digital transformation and customer concentration: An examination based on dynamic capability theory - Liu, Laihui; An, Suxia; Liu, Xiangyu (Frontiers in Psychology, 2022)
Digital transformation of traditional enterprises can better develop new customer relationships and help mitigate the business risk of their over-reliance on single-customer relationships. However, little research has been conducted on the internal mechanisms of how enterprise digitalization reshapes corporate customer relationships. In this manuscript, from the perspective of dynamic capability theory, we construct conceptual models of enterprise digital transformation, innovation capability, operational cost, and customer satisfaction, and explore the internal mechanisms of enterprise digital transformation to reduce the dependence of enterprises on large customers. The model is empirically studied by obtaining data on the degree of digital transformation of enterprises through “search statistics” of keywords in the annual reports of Chinese listed companies during 2011–2019. This manuscript finds that digital transformation significantly reduces the concentration of large customers and has become a powerful driver of business model innovation in the digital economy, and this finding remains robust to the use of PSM and instrumental variable methods to address endogeneity. Digital transformation reduces firms’ dependence on large customers through three mechanisms: improving firms’ innovation capabilities, reducing firms’ operating costs, and increasing customer satisfaction. The impact of digital transformation on reducing the dependence of non-state enterprises on large customers is greater than that of state-owned enterprises; the implementation of digital transformation strategies is more helpful for enterprises that have active interactions with customers to reduce their customer concentration; and the reduction of customer concentration is greater for enterprises in regions with higher levels of digital development compared to those in regions with lower levels of digital development. The economic consequence test finds that digital transformation diversifies customer structure and reduces business risks. The analysis of the innovation effect and customer satisfaction effect on reducing the concentration of large customers of enterprisesby implementing digital transformation enriches and expands the dynamic capability theory and provides important insights for enterprises to diversify their customer structure.